PENGARUH KEPEMIMPINAN DEMOKRATIS, TRANSPARANSI ORGANISASI, PENGHARGAAN TERHADAP LOYALITAS KARYAWAN DAN PENINGKATAN LAYANAN TEKNIK DENGAN USIA DAN TINGKAT PENDIDIKAN SEBAGAI VARIABEL PENGONTROL DI PERUSAHAAN LISTRIK NEGARA - Irayanti, Adinda; Hamada, Abubakar; Nafi’uzzaki, Anang; Amiq, Bahrul; Andriannoor, Renaldy; Fahmi Hasan, Fuad; Setiawan, Wawan; Rahmawati, Imelda Dian (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
This study examines the impact of democratic leadership, organizational transparency, and rewards on employee loyalty and technical service improvement at Perusahaan Listrik Negara (PLN), with age and education level as control variables. As a state-owned enterprise, PLN's success in delivering quality electricity services depends heavily on employee performance, particularly in technical operations. Democratic leadership, which promotes employee participation in decision-making, and organizational transparency, which fosters trust and engagement, are expected to enhance employee loyalty and motivation. Additionally, rewards—both material and non-material—are seen as key drivers of dedication and service quality. Employee loyalty, in turn, plays a critical role in improving the quality of technical services provided by PLN. The study also considers how demographic factors such as age and education influence how employees respond to organizational policies and leadership styles. The findings aim to provide insights for PLN to improve employee performance and enhance service quality.